Natal environmental conditions modulate senescence of antler length in roe deer - Cambreling, Solène; Gaillard, Jean-Michel; Pellerin, Maryline; Vanpé, Cécile; Débias, François; Delorme, Daniel; Garcia, Rébecca; Hewison, A. J. Mark; Lemaître, Jean-François (Frontiers in Ecology and Evolution, 2023)
It is now broadly admitted that female reproductive senescence – a decline in reproductive performance with increasing age – occurs in most species, at least among birds and mammals. Although information is more limited, male reproductive senescence has been regularly inferred from the decline in the size or performance of phenotypic traits that underly male reproductive success, particularly secondary sexual traits. However, the degree to which environmental conditions influence the pattern of senescence in sexual traits remains largely unknown. From the analysis of two long-term studies of populations of European roe deer (Capreolus capreolus) subjected to markedly different environmental contexts in the wild, we tested the hypothesis that harsh natal and/or current conditions should lead to earlier and/or stronger rates of senescence in the length of fully-grown antlers than good natal and/or current conditions. We found evidence of similar patterns of antler length senescence in both populations, with an onset of senescence around 7 years of age and a decrease of length by about 1–1.5 cm per additional year of life from 7 years of age onwards. We found that good early-life conditions delay senescence in antler length in roe deer. Our results also revealed that senescent males seem to be unable to allocate substantially to antler growth, confirming that antler size is, therefore, an honest signal of male individual quality. By modulating age-specific allocation to secondary sexual traits, natal and current conditions could influence female mate choice and male–male competition over mates, and as a result age-specific reproductive success, and should be accounted for when studying the dynamics of sexual selection.